Response of Microbial Compositions and Interactions to Biochar Amendment in the Peanut-Planted Soil of the Yellow River Delta, China - Sun, Ruixue; You, Xiangwei; Cheng, Yadong; Gan, Deping; Suo, Fengyue; Wang, Bo; Li, Yiqiang (Frontiers in Environmental Science, 2022)
Coastal soils in the Yellow River Delta (YRD) are characterized by high salinity and degraded physicochemical properties, which threaten agricultural production. Biochar has received growing interest as a sustainable soil amendment. However, the effects of biochar on coastal soil quality and the soil microbial response in the field are limited. In this study, the responses of soil properties and microbes to biochar amendment at low dosage (LBC, 18 ton/ha) and high dosage (HBC, 36 ton/ha) and no biochar treatment (CK) were investigated in a peanut field located in the YRD. The results elucidated that biochar-amended soils showed higher available nutrient (i.e., nitrogen, phosphorus, and potassium) contents and cation exchange capacity, but exhibited lower electrical conductivity. Generally, the bacterial community was more easily impacted than that of fungi in both LBC and HBC treatments. Furthermore, the LBC amendment not only improved the abundance of some beneficial bacteria (i.e., Sphingomonas and Nannocystis) but also increased the complexity, modularity index, and competitive interactions of the bacterial co-occurrence network. HBC-enriched Rozellomycota that is probably associated with peanut rot decreased the modularity index and competitive interactions, which might account for the decreased peanut yield under HBC treatment. It is encouraged to comprehensively consider the interaction among microorganisms when evaluating the effects of soil amendments on the soil environment, which plays a vital role in rhizosphere microecology and soil quality.